The contribution of Zvishavane community share ownership trust on youth empowerment in Zvishavane district - Manata, Tatenda (Midlands State University, 2017)
The aim of this research is to assess how ZCSOT has contributed to youth empowerment within Zvishavane District using Dayataya ward as reference. In particular youth empowerment was looked at from the perspective of five different capitals which are social, physical, human, financial and natural capital as provided for in the Sustainable Livelihoods Framework. The general objective was to look at how ZCSOT has promoted youth empowerment and assess failures in cases where they have not been influential as well as giving possible recommendations on how youth empowerment can be improved as one of the developmental aspects. Qualitative methodology was used during the study with two types of data gathering instruments employed, these are questionnaires and interviews. A total of thirteen questionnaires were made use of together with twenty interviews being carried out, making the target population thirty three in total. Purposive type of sampling was used and respondents were chosen from youths within Dayataya ward, ZCSOT employees, and MYIEE district head and youth officers within the ward. Results from the study shows that ZCSOT has made considerable efforts to improve the lives of youths through various development indicators like improved infrastructure, employment creation, increased ground for youth participation, and provision of safe drinking water as well as improved healthcare facilities or clinics and educational development. However, it has been noted that there are various challenges facing youths in accessing help from ZCSOT which are lack of transparency and accountability, empty promises from the Trust, complicated governance issues, lack of implementation of youth centred and sustainable as well as failure of ZCSOT to meet their obligations on youth empowerment